Analisis Penggunaan Bilingualisme dan Diglosia pada Tindak Tutur Sehari-hari Siswa SMPN 3 Kelumpang Tengah Kabupaten Kotabaru - Normasunah Normasunah (CENDEKIA: JURNAL ILMIAH PENDIDIKAN, 2020)
This study aims to describe the use of bilingualism and diglossia in the daily speech acts of students of SMPN 3 Kelumpang Tengah Kotabaru district. This type of research used in this study is the type of field research and the method used in this study is a qualitative descriptive method. The descriptive qualitative method in this study was assisted with a quantitative data presentation. The results showed that the use of bilingualism and diglossia in daily speech acts of students of SMPN 3 Kelumpang Tengah Kotabaru district, namely; (1) the use of bilingualism in daily speech acts of SMPN 3 Middle Kelumpang students in Kotabaru district as much as 36% is in the low criteria; (2) the use of diglosia in the daily speech acts of students of SMPN 3 Kelumpang Tengah Kotabaru district as much as 64% are included in the high criteria. Keywords: bilingualism, diglosis, speech acts